Mechanical response of existing tunnels for shield under-crossing in cobble strata based on the model test. (July 2022) - Lin, Qingtao; Lu, Dechun; Lei, Chunming; Tian, Yu; Kong, Fanchao; Du, Xiuli
Abstract: A model test of shield under-crossing in cobble strata is conducted, based on the self-designed earth pressure balance (EPB) shield platform, to analyse mechanical response of the existing tunnel. The test model includes two existing tunnels, i.e., a horseshoe tunnel and a rectangular tunnel, which are designed by taking the interval tunnel of Beijing metro line 10 as background. The earth pressure acting on the existing tunnel, longitudinal strain of the top plate and base plate of the existing tunnels, and circumferential strain in the central cross-section of the existing tunnels, are measured during the shield under-crossing process. Based on the measured results, variation law of the earth pressure on the existing tunnels and their deformation feature along the longitudinal and circumferential direction during the whole shield advancing process are revealed. The deformation difference between the horseshoe tunnel and rectangular tunnel is found, and the weak positions in the two existing tunnels are pointed out.